DEVELOPING INTEGRATED ENGLISH SYLLABUS FOR MARINE SCIENCE STUDENTS AT BENGKULU UNIVERSITY - Vina Febrianty; Syahrial Syahrial; Alamsyah Harahap (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2022)
An Integrated English Syllabus is a syllabus that integrate one to several language skills of learning and teaching process. They cover elements of English skills, English materials, learning techniques, and so on. In this study, the researcher use Research and Development method by Sugiyono (2010). The purposes of this study are to find out the English skills and the English materials that really needed by Marine Science Students. In addition, focuses on developing an Integrated Syllabus with Marine Science context. In designing Integrated Syllabus the researcher use integrated model by Richard (2001). To collect the data the researcher use interview and questionnaire. The parcipants are 1 English lecturer, 1 Marine Science Lecturer, 2 stakeholders (Water and Marine Police at Pulau Baai Bengkulu and Employee at Marine Affairs and Fisheries at Bengkulu Province), and 8th semester Marine Science Students at Bengkulu University. The result of this study showed that the Marine Science students needs the four of English skills and English materials but  the most needed are writing and reading. Therefore, the researcher designed an Integrated Syllabus that is suitable with Marine Science Study Program especially at Bengkulu University. From the research, it can be seen that the English needs of marine science students at Bengkulu University. Then, the syllabus developed in this study can be used as a reference in preparing English courses in the Marine Science study program.